DETERMINAN RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2017 - Riska Hanifa Rahmawati, 14.05.52.0181; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the factors that influence stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The independent variables used in this study are current ratio, solvency ratio, profitability ratio, asset turnover and firm size. While the dependent variable used in this study is stock returns. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The sampling method in this study used a purposive sampling method with a total sample of 126 companies. The analytical tool used is multiple linear regression analysis using the SPSS program. The results of the study show that the variable size of the company and asset turnover have a significant effect on stock returns. While the current ratio variable, Debt to Equity Ratio and Return on Asset do not have a significant influence on stock returns.